Glocal Evaluation Competencies for Learning As We Go: Zooming in and zooming out to connect system-level solutions to local beneficiaries - Keiko Kuji-Shikatani; Charmagne Campbell-Patton; Wendy Rowe (Journal of MultiDisciplinary Evaluation, 2023)
Identifying essential competencies for evaluators has received significant attention in recent years yet practical examples of how to apply competencies to real-time learning in complex environments are lacking. In particular, the experience of those at the local level - ultimate beneficiary individuals (UBIs) - can get lost when evaluations take a systems perspective. Experienced evaluators share how Learning as we go is used to describe utilization-focused developmental evaluation embedding evaluative thinking and building capacity in public sector programs, that support learning and adaptation to improve the lives of those most impacted by inequitable and unsustainable global systems.